"Authority must be on the side of freedom": The relationship between teachers' authority and Black and Latinx students' political agency in challenging racism. Issue 4 (2nd October 2021) - Graves, Daren
ABSTRACT: In order to position Black and Latinx youth to challenge racism and other dynamics of oppression, their education must be oriented toward equipping them with the requisite skills and sense of efficacy. This article makes an argument for teachers having to develop a reciprocal sense of authority rooted in their students' freedom in the face of oppressive systems. Drawing on the author's previous researchthis paper illustrates that educators who are reflective about their own positionalities, pair the study of racism with resistance strategies, and who make space for students to resist racism, created authentic opportunities for their Black and Latinx students to develop political agency in challenging racism.